Flexible for whom? Flex crops, crises, fixes and the politics of exchanging use values in US corn production. Issue 1 (2nd January 2016) - Gillon, Sean
Abstract : Flexible allocation of crops among food and non-food uses is a key driver of global agri-food system change. Focusing on United States corn production, I explore the dynamics of flex crops, scrutinizing agri-industrial relationships and the distribution of agri-food system value and control. I situate crop flexing as exchanging use value, as opposed to converting use into exchange value without altering the commodity's use. Asking 'Flexible for whom?' in the context of agri-food system crises, I find: (1) flex crops exacerbate contradictory food security and over supply crises, and that the distribution of flexibility and benefit in the agri-food system they provide depends on the organization of labor; (2) crises of accumulation tie flex crops to agri-food system financialization, which subordinates use to exchange value, obfuscating their relationship and distancing agricultural products and uses from their basis in nature and labor; and (3) debates over US corn flexing illustrate the utility of focusing on power and politics in crop flexing decisions and demonstrate US corn flexing to be a fix for climate and accumulation crises. Findings suggest that examining the distribution of value and control and the positions of labor and nature in the agri-food system may be productive for global flex crop research and advocacy in the future.